2020
DOI: 10.3390/s20051381
|View full text |Cite
|
Sign up to set email alerts
|

WiFi-Based Driver’s Activity Monitoring with Efficient Computation of Radio-Image Features

Abstract: Driver distraction and fatigue are among the leading contributing factors in various fatal accidents. Driver activity monitoring can effectively reduce the number of roadway accidents. Besides the traditional methods that rely on camera or wearable devices, wireless technology for driver’s activity monitoring has emerged with remarkable attention. With substantial progress in WiFi-based device-free localization and activity recognition, radio-image features have achieved better recognition performance using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Typically, a pair of conductive silver/ silver chloride electrodes are integrated into flexible three-electrode system to prepare wearable "tattoos" and "patches" based on screen printing technology. Then, wireless transmission devices, such as WiFi, 139 Bluetooth, 27 and NFC module, 140 been applied in glucose 74 and lactic acid detection. 143 The first wearable current biosensor was used for glucose detection.…”
Section: Electrochemical Signal Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Typically, a pair of conductive silver/ silver chloride electrodes are integrated into flexible three-electrode system to prepare wearable "tattoos" and "patches" based on screen printing technology. Then, wireless transmission devices, such as WiFi, 139 Bluetooth, 27 and NFC module, 140 been applied in glucose 74 and lactic acid detection. 143 The first wearable current biosensor was used for glucose detection.…”
Section: Electrochemical Signal Modulementioning
confidence: 99%
“…Typically, a pair of conductive silver/silver chloride electrodes are integrated into flexible three‐electrode system to prepare wearable “tattoos” and “patches” based on screen printing technology. Then, wireless transmission devices, such as WiFi, 139 Bluetooth, 27 and NFC module, 140 are integrated and transmit signals to the terminals (e.g., laptops, computers, and mobile phones) for continuous tracking and monitoring changes in electrical signals. According to the principle of signal change, the electrochemical response signal includes current, potential, and electrical impedance.…”
Section: Signal Modules For Wearable Biosensorsmentioning
confidence: 99%
“…In recent decades, WiFi-based driver's in-vehicle activity and gestures recognition systems have been introduced with good recognition performance [50][51][52]. WiFind [36] presented a WiFi CSI-based driver fatigue detection system.…”
Section: Related Workmentioning
confidence: 99%
“…In our presented framework, all experiments are performed with 802.11n enabled WiFi devices as described in [50][51][52]. Specifically, a laptop is used as a receiver that is equipped with Intel 5300 NIC and three receiving antennas, i.e., ℕ Rx = 3.…”
Section: Experimentation Settingsmentioning
confidence: 99%
“…Inattention detection systems can be classified into two categories according to the types of their input signals. One category uses vehicle signals such as the speed and steering angle [ 2 , 3 , 4 , 5 , 6 , 7 ]. Kume et al [ 3 ] reported that the sensitivity of detecting an inattentive state using in-vehicle sensors was 53% with a fixed threshold, and 82% with a manually set threshold.…”
Section: Introductionmentioning
confidence: 99%